Second highly modified hypogean species of the genus Morimotoidius Habu from western Jiangxi Province, China, with a new locality for M. zhushandong (Coleoptera: Carabidae: Platynini) - Wang, Xinhui; Pang, Jianmei; Tian, Mingyi (Zootaxa, 2015)
Morimotoidius cavicola sp. n. is described and illustrated from a limestone cave called Guanfeng Dong in Yichun City of western Jiangxi Province, China. It is the second hypogean and highly morphologically modified species of the genus Morimotoidius recorded in China. M. cavicola sp. n. is easily recognized by its shorter pronotum which is less expanded medially than that in M. zhushandong Pang & Tian, 2014. M. zhushandong is also recorded from the cave Zhuangxi Dong. A distribution map, together with a modified key to Chinese species of the genus are also provided.